Smart Contact Lens with Dual‐Sensing Platform for Monitoring Intraocular Pressure and Matrix Metalloproteinase‐9. Issue 12 (23rd February 2022) - Ye, Ying; Ge, Yuancai; Zhang, Qingwen; Yuan, Meiling; Cai, Yu; Li, Kang; Li, Yang; Xie, Ruifeng; Xu, Changshun; Jiang, Danfeng; Qu, Jia; Liu, Xiaohu; et al.
Abstract: Contact lenses have become a popular health‐monitoring wearable device due to their direct contact with the eyes. By integrating biosensors into contact lenses, real‐time and noninvasive diagnoses of various diseases can be realized. However, current contact lens sensors often require complex electronics, which may obstruct the user's vision or even damage the cornea. Moreover, most of the reported contact lens sensors can only detect one analyte. Therefore, an optical‐based dual‐functional smart contact lens sensor has been introduced to monitor intraocular pressure (IOP) and detect matrix metalloproteinase‐9 (MMP‐9), both of which are key biomarkers in many eye‐related diseases such as glaucoma. Specifically, the elevated IOP is continuously monitored by applying an antiopal structure through color changes, without any complex electronics. Together with the peptide modified gold nanobowls (AuNBs) surface‐enhanced Raman scattering (SERS) substrate, the quantitative analysis of MMP‐9 at a low nanomolar range is achieved in real tear samples. The dual‐sensing functions are thus demonstrated, providing a convenient, noninvasive, and potentially multifunctional sensing platform for monitoring health and diagnostic biomarkers in human tears. Abstract : Intraocular pressure (IOP) and matrix metalloproteinase‐9 (MMP‐9) are biomarkers closely associated with ocular diseases. A dual‐functional contact lens sensor for detections of both biomarkers, using structural colors and peptides modified surface‐enhanced Raman scattering (SERS) substrate, respectively is reported. This optical sensor, therefore, provides a potentially versatile, noninvasive sensing platform for detecting multibiomarkers of human eye diseases.